A influência de eventos exógenos no aumento de rentabilidade das empresas privatizadas na fase manufatureira do PND. - Soares, Selene de Souza Siqueira (2007)
Privatization policy spread out worldwide in the last decades on the 20th century. The process that was initiated in the 1970s during the Thatcher Government in Britain grew rapidly. In Brazil, between 1991 and 2000, over 130 public companies were sold to the private sector resulting in US$ 87,2 billion revenue. This dissertation intends to discuss and evaluate in a quantitative way how phenomena which were considered exogenous to the ownership exchange influenced the financial performance of the privatized companies at the manufacturing phase of the Brazilian Privatization Program. One of the most frequent arguments in favor of private ownership is the increase in profits. In Brazil, most companies sold at the manufacturing phase of the Brazilian Privatization Program experienced expressive improvement in their financial performance in the 1990s. Several authors attribute the positive results that privatized companies achieved to the increase in their internal efficiency associated with new management pattern. This work shows that apart from these elements, other events exogenous to the exchange in the ownership highly contributed to improvement on their economical performance. This work focus on the main companies privatized at the manufacturing phase. This selection is important and necessary. It is important because it refers to companies that play relevant roles in the national industrial complex in terms of production, as well as in revenue and assets. On the other hand, this selection is necessary because it assures a homogenous sample. All of them present the same manufacturing characteristics and faced a rather fast exchange ownership process under similar institutional apparatus. The results indicate that around 73% of the profits increas were due to exogenous factors for the analyzed companies. The steel industry was the sector that relied on the largest share in this type of events, scoring 80% of participation on the total variation of the operational cashflow between 1990 and 1994, followed by oil sector for which exogenous factors represent almost 36% of the explained total of variation in operational cashflow between 1991 and 1995. The aeronautic material sector presented values around 16% of share in exogenous events in the results between 1993 and 1998.